SPATIAL MICROBIOLOGICAL ANALYSIS OF WATER SOURCES IN PUBLIC SECONDARY SCHOOLS IN SOKOTO METROPOLIS - Lawal, Nasiru; Dadan-Garba, Aliyu; Ajibuah, Bolanle Joel; Oluwole, Olumide Akinwumi (FUDMA JOURNAL OF SCIENCES, 2024)
This study aimed to assess the water quality in public secondary schools within Sokoto Metropolis, Nigeria, with a focus on evaluating microbial contamination levels and identifying spatial disparities in water facilities. Comprehensive assessment checklist based on WHO and UNICEF standards was used to evaluate the availability and adequacy of water facilities. Water samples were collected from 13 public secondary schools using a stratified and proportionate sampling techniques, ensuring representation across different water sources, including boreholes, pipe-borne water, and dug wells. The samples were then transported to the Sokoto State Water Board laboratory for microbial testing. The analysis specifically targeted the presence of indicator bacteria, including Escherichia coli (E. coli), total coliforms, and fecal streptococcus, to assess the microbial quality of the water sources. The findings revealed significant spatial disparities in the distribution of schools and highlighted areas with inadequate water facilities. Microbial analysis indicated varying levels of contamination across the different water sources, with dug wells having the highest E. coli count, averaging 11.33 CFU/100ml. The total average E. coli count across all water sources was 6.08 CFU/100ml, which exceeds the Nigerian Industrial Standard (NIS) Maximum Permissible Limit (MPL) of 0 CFU/100ml, indicating a concerning level of contamination. These results suggest a substantial risk to public health, particularly for students and staff relying on these water sources. The study emphasises the urgent need for interventions such as reconstruction and rehabilitation of water infrastructure and regular water quality testing to ensure safe drinking water is provided in public secondary schools in...
Keywords: E. Coli; Contamination; Water quality; Public Secondary School; Sokoto metropolis